2019
DOI: 10.1038/s41375-019-0612-8
|View full text |Cite
|
Sign up to set email alerts
|

How we use venetoclax with hypomethylating agents for the treatment of newly diagnosed patients with acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is associated with poor outcomes, especially in older patients in whom the disease is most common. B-cell lymphoma 2 (BCL-2) is an antiapoptotic protein involved in the survival and maintenance of AML, and it is overexpressed in the leukemia stem cell population. Venetoclax is an oral BCL-2 protein inhibitor recently approved by the United States Food and Drug Administration (FDA) for use in combination with a hypomethylating agent (HMA) (azacitidine or decitabine) or low-dose cyta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(121 citation statements)
references
References 48 publications
6
115
0
Order By: Relevance
“…The median follow-up was 15.1 months, and the median OS for all groups was 17.5 months. In addition, the patients who received 400 mg venetoclax plus HMA achieved a remarkable CR/CRi rate of 73% (76% for azacitidine and 74% for decitabine), which revealed that the combinations with azacitidine or decitabine were not significantly different and that 400 mg of venetoclax might be a favorable dose (84,85). Furthermore, patients with IDH1/2 mutations, FLT3 mutations, or NPM1 mutations had CR/CRi rates of 71%, 72%, and 91.5%, respectively.…”
Section: Venetoclax-based Combinations In Treatment-naïve Patients Wimentioning
confidence: 95%
“…The median follow-up was 15.1 months, and the median OS for all groups was 17.5 months. In addition, the patients who received 400 mg venetoclax plus HMA achieved a remarkable CR/CRi rate of 73% (76% for azacitidine and 74% for decitabine), which revealed that the combinations with azacitidine or decitabine were not significantly different and that 400 mg of venetoclax might be a favorable dose (84,85). Furthermore, patients with IDH1/2 mutations, FLT3 mutations, or NPM1 mutations had CR/CRi rates of 71%, 72%, and 91.5%, respectively.…”
Section: Venetoclax-based Combinations In Treatment-naïve Patients Wimentioning
confidence: 95%
“… 28 30 ). Reflecting the dearth of effective new agents for older patients with AML, in November 2018, the FDA awarded accelerated approval to venetoclax in combination with azacitidine, decitabine, or LDAC in untreated patients with AML aged ≥75 years, or in patients with comorbidities that preclude the use of intensive induction chemotherapy 31 . The sustained future of venetoclax in previously untreated patients with AML considered ineligible for intensive chemotherapy due to age or comorbidities has been reinforced by the positive outcome from the recently completed randomized phase 3 study that evaluated azacitidine (VIALE-A) with or without venetoclax, with OS as the primary endpoint 26 .…”
Section: New Treatment Options For Older Unfit Patients With Amlmentioning
confidence: 99%
“…In terms of the time required to identify a targetable mutation in a newly diagnosed patient with AML, retrospective analyses suggest that patient outcomes are not compromised by a short delay from the time of diagnosis to commencement of induction treatment, both in younger and older patients, when monitored closely 49 . Thus, a valid approach would be to first identify patients with nonproliferative, stable disease able to wait for 5–10 days with close monitoring (the overwhelming majority of new AML patients), to enable identification and selection of an optimal induction regimen 31 , 49 .…”
Section: Could Biologically Directed Therapies Deprioritize Traditionmentioning
confidence: 99%
“…Given these results, the success of the combination of venetoclax with a hypomethylating agent (HMA) (either 7 d of azacitidine or 5 d of decitabine) or low-dose cytarabine in newly diagnosed, elderly AML patients was somewhat unexpected. Studies have demonstrated 50%-70% response rates for combination therapy in this high-risk population[ 47 , 48 ]. In addition, in the HMA + venetoclax study, median overall survival was increased by 17.5 mo (double that of an HMA alone)[ 47 ].…”
Section: Targeting B-cell Lymphoma-2 In Acute Myeloid Leukemiamentioning
confidence: 99%